The paediatric surgeon and his working conditions in Francophone sub-Saharan Africa - K Gnassingbé; H Tekou; S da Silva-Anoma; G K Akakpo-Numado; C Aguehounde; R Dick; R Bankole; H Abarchi; A Wandaogo; O Ouattara; D B Kouame; M N'Doye (Wolters Kluwer Medknow Publications, 2011)
Background: This study described the current conditions of work of paediatric surgeons in Francophone sub-Saharan Africa (FSSA) and set the debate at the level of the humanist thinking in medicine. Patients and Methods: This was a multicentre study from 1 st May to 30 th October 2008. The African Society of paediatric surgeons' directory was used to identify paediatric surgeons in the Francophone's countries in Sub Saharan Africa. The parameters studied were number of surgeons per country, means of training, working conditions, remunerations, needs for continuous training and the research. Results: A total of 41 paediatric surgeons (68.33%) responded. The average number of paediatric surgeons per country was 5. The means of training included government scholarships among 7 paediatric surgeons (17.07%), scholarship from a non-governmental organisations in 14 (34.15%) and self-sponsorships in 20 (48.78%). The average salary was 450 Euros (€) (range: 120-1 400 Euros). Most of the paediatric surgeons (68.29%) had internet services for continuous update courses and research. Thirty six paediatric surgeons (87.80%) had no subscription to specialised scientific journals. Conclusion: The paediatric surgeon in FSSA faces many problems related to his working and living conditions that may have a negative impact on their competences.